Hazards Caused by Uncontrolled Vegetation and Inadequate Maintenance Practice in Earth Dams - Escolano Sánchez, Félix; Fernández Serrano, Roberto (Tecnología y ciencias del agua, 2015)
Small dams for irrigation use are often managed by landowner communities. Dam owners are responsible for the routine maintenance actions of each dam and their common irrigation system net. Due to various social factors, like population ageing or farming loss, in areas where there has been a notable decline of agriculture, the maintenance activity of the irrigation hydraulic net is defectively conducted. An inadequate practice of maintenance first allows the growth of vegetation which may develop over the dam embankment surface, affecting to the compacted earth structure. Trees and big shrubs that grow on dam slopes and crest may have a negative impact on certain geotechnical aspects. Apart from vegetation, once that owners neglect their maintenance obligations, animal invasion or human wrong uses go with vegetation growth. The paper shows frequently found vegetation impacts observed in Spain, along with animal or human impacts, which may involve geotechnical problems. General conclusions and recommendations have been proposed in order to help owners to maintain their dams and to avoid long term problems.